Surgical outcome in germ cell tumor of ovary - R., Pooja; Patil, Varsha Narendra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Ovarian cancer accounts for 225,000 new cases and 140,000 deaths every year. Ovarian germ cell tumors account for 15-20% of all ovarian malignancies and incidence of malignant ovarian germ cell tumors is 2-6%. These tumors typically occur in adolescent girls and young women. Appropriate fertility conserving surgical treatment for patients where fertility needs to be preserved and resection of all visible disease can be successfully performed. For patients with advanced-stage disease, debulking surgery is done. Methods: Current study is a retrospective study. The present study was conducted in the department of obstetrics and gynecology, Cama and Albess hospital, Mumbai, Maharashtra, India, from a period of May 2019 to December 2021. This study was conducted with 30 patients to evaluate the outcome in operated cases of germ cell tumors of ovary. Results: Majority of the patients (30%) were in the age group of 31-40 years, 17 (56.7%) patients were unmarried while 13 (43.3%) patients were married. The most common symptom was abdominal mass and pain (86.7%). The most common histologic type was dysgerminoma (46.7%). Out of total 19 patients with FIGO stage I, 13 patients (68.4%) underwent Fertility sparing surgery (FSS) and 6 patients (31.6%) underwent non fertility sparing surgery (non-FSS). Conclusions: Surgery has an important role in the management of germ cell tumors. Initial careful surgical staging is of great importance for appropriate subsequent therapy. Fertility sparing surgery is feasible in most cases. Malignant ovarian germ cell tumors have excellent prognosis for stage I and for advanced stages.